Small Shifts, Big Impacts: Cultivating Intercultural Skills Through Online Global Classrooms - Khokhar , Ashar Johnson (Journal of Communication and Cultural Trends, 2026)
This study explores the impact of a structured intercultural learning (IL) intervention on students’ intercultural competence (IC) across Global Liberal Arts Alliance (GLA) member institutions. Implemented through the Global Course Connection (GCC) initiative, the intervention was evaluated using a pre-experimental, single-group pre-post design. A total of 178 undergraduate students from humanities, sciences, and social sciences completed the Intercultural Sensitivity Scale (ISS) before and after participating in the program. Results showed a modest but meaningful improvement (5%–7%) in students’ attitudes and behaviors related to IC, including cultural respect, confidence, engagement, and enjoyment. There was also a notable decline in negative attitudes like ethnocentrism and avoidance. The study confirms that even short-term, curriculum-embedded interventions can foster IC in diverse educational settings. It also highlights the importance of virtual international collaborations such as COIL, particularly for Global South institutions with limited access to physical exchange opportunities. Furthermore, the study calls for integrating reflective social media use into IC education, acknowledging its role in shaping students’ worldviews. The findings support expanding structured IL programs and enhancing North–South academic partnerships to cultivate globally competent graduates who are prepared to navigate and contribute to multicultural societies.